Análise do modelo de capacidade de infiltração variável (VIC) para as bacias dos rios Santa Maria da Vitória e Jucu - Campanharo, Wesley Augusto (2013)
Hydrological modeling is a technique that enables a better understanding and representation of the hydrological behavior of watersheds. The Variable Infiltration Capacity (VIC) is a macroscale model, which simulates vertical transfer water and energy processes. The objective of this study was to evaluate the applicability of the VIC for two watersheds that the government of Espírito Santo made priority basins for hydrological study: Jucu and Santa Maria da Vitória. Therefore we obtained information of soil, vegetation and climatic, which were then aggregated to elevations data for obtain flow data simulated. Initially was separated 5 years of weather data (1992 a 1996) for the calibration process involving both obtaining the best resolution, as the best combination of parameters calibrated. This selection process was through the correspondence between the observed and simulated flows. Having the best combination found for each gaging station, began the validation process, which consisted of verifying the adherence of the model using a new series of 5 years (1997 a 2001). With the best resolution/combination was performed simulations of changes landscape, with three different scenarios of use and vegetation cover: CM1- considerer the application of ecological corridor’s project; CM2 – considerer the increase of 20% of forestry; CM3 – considerer the increase of 50% of forestry. For the 1024 combinations tested, only for the Santa Maria station inside the Santa Maria da Vitória basin was observed positive values of Nash. The validation process showed the same behavior, but the simulation of low and medium flows had better results. When analyzing the changes in flux rates from each simulated scenario, observed a decrease in runoff while increase the forest cover. The present work was unsatisfactory for two of three checkpoints and for simulation of low and medium flows, and may be can be a reflection of the type of calibration, together with the set of possible errors inherent in input files and/or deficiency of hydrological model parameterization.